Hadzic's peripheral nerve blocks and anatomy for ultrasound-guided regional anesthesia - Hadzic, Admir; New York School of Regional Anesthesia (New York : McGraw-Hill Professional, 2012)
"Hadzic's Peripheral Nerve Blocks delivers practical, state-of-the-art guidance for all major nerve block procedures, including ultrasound-guided nerve blocks. A standardized,user-friendly presentation provides meticulous, step-by-step instructions for each procedure. The second edition has been completely updated to include new developments, the latest equipment, and hundreds of new photographs"--Provided by publisher
Foundations of peripheral nerve blocks -- Nerve stimulator and surface-based nerve block techniques -- Intravenous regional anesthesia -- Foundations of ultrasound-guided blocks -- Ultrasound-guided nerve blocks -- Ultrasound-guided neuraxial and perineuraxial blocks -- Atlas of ultrasound-guided anatomy -- Atlas of surface anatomy
Rev. ed. of: Peripheral nerve blocks : principles and practice. c2004
Includes bibliographical references and index
13
Keywords: Nerve block; Nerve block; Nerve Block -- methods; Peripheral Nerves -- anatomy & histology; Peripheral Nerves -- ultrasonography; Ultrasonography -- methods